UNDERSTANDING AND AWARENESS OF GENDER EQUALITY IN DIVORCE AND ITS CONTRIBUTION TO ISLAMIC FAMILY LAW REFORM IN INDONESIA - Hidayat, Eko; Mahmudah, Siti (Universitas Islam Negeri Raden Intan Lampung, 2022)
The formation of a family through marriage does not always go well, and it cannot be denied that when forming a marriage bond there are problems that must be lived by both of them. This happens due to various factors in the family. Conflict and discord lead to the end of the family through divorce as a last option. This is what happened in Lampung Province, where 17,229 divorce cases were registered in 14 Religious Courts during the period from January to November 2021. This research is a qualitative descriptive-analytic research.These research data collection methods are observation, interview, and documentation. The data analysis method used is qualitative analysis, and conclusions are drawn using inductive thinking. The results of the study show that the dominant factor influencing divorce in Lampung Province is the economic factor. Understanding and awareness of gender equality among divorcees in Lampung Province indicated that respondents had awareness and understanding of gender, but their partners did not want gender equality. Based on this, it is necessary to accommodate the principles of justice and gender equality in order to realize the goal of marriage to form a happy and eternal household with the addition of the principle of preventing violence in marriage as part of the principles of marriage.